I am worth more and I deserve more - Sumairi, Sri Sunarti; Hashim, Junaidah; Ismail, Yusof (Management Centre, IIUM, 2013)
This case highlights issues related to the worth of a job. It is a challenging task to recognise additional tasks done by employees, especially if the tasks are not stated in the job description and not evaluated; therefore results and outcomes are not compensated. Employees tend to question the employer’s individual equity on them as well as the expectations of employers and the basis of compensation/recognition. Employees tend to compare their compensation with those of their internal colleagues as well as those of their external peers, that is, friends who work for other organisations. Unfair compensation packages will lead to job dissatisfaction and a loss of talent in the company concerned.